Effect of different planes of nutrition and mineral supplementation on nutrient utilization and semen quality of Frieswal bulls - GIRDHAR, NARESH; PRASAD, R; KUMAR, MAHESH; SINGH, KRIPAL (The Indian Journal of Animal Sciences, 2011)
Adult Frieswal bulls (12) of approximate similar age (2–2.5 years) and body weight (450 kg) were divided into 3 groups of 4 animals each. The bulls were selected from the lot whose semen as per normal standard was not freezable. Bulls of group 1 were fed as per Military farm feeding schedule, group 2 were fed as per NRC and group 3 at 20% higher energy level of NRC. Each group was further divided into 2 sub-groups A and B. In sub-group A (Min I), mineral supplementation was 0.8% of total diet and in sub-group B (Min II), mineral supplementation was 1.2% of total diet. The feeding of roughages, green fodder and concentrate mixture was done as per the requirement of animals with regular monitoring of body weights. A feeding trial of 8 months was carried out. After a feeding period of 90 days, a digestibility trial of 6 days duration was conducted on all the animals. The dry matter intake of the bulls per 100 kg body weight was 2.01, 1.86 and 2.02 kg in groups 1, 2 and 3 respectively. The dry matter (DM), organic matter (OM), neutral detergent fibre (NDF) and acid detergent fibre (ADF) digestibility was significantly higher in the animals of group 3 as compared to group 1. Effect on various semen quality parameters of bulls under trial was also carried out. Between the different months there were fluctuations regarding these parameters. However at the end of seventh month the seminal volume increased in all groups. Mass motility also increased in groups 1 and 2 while there was decrease in group 3. Concentration of sperms in groups 1 and 2 also increased at seventh month of collection compared to at first month. Mineral addition at 50% over and above to normal diet also had positive effect on per cent sperm motility, which increased in Min II group (supplemented group) from 36.23 to 50.00 compared to Min I group (control group). Similarly there was increase in mass motility and sperm concentration in the semen of animals of Min II group as compared to Min I group at seventh month of collection as compared to first month of collection. The freezing percentage was better in the animals given additional mineral supplementation as compared to normal group animals.